A buccal mucosal graft subcoronal resurfacing technique to treat recurrent penile adhesions: the buccal belt. (30th December 2021) - Beamer, Matthew R.; Angulo, Javier C.; Capiel, Leandro; López‐Alvarado, Damian; Ramirez, Erick A.; Satyagraha, Paksi; Zaccarini, Daniel; Kittleman, Michelle A.; Nikolavsky, Dmitriy
Abstract : Objective: To outline our step‐by‐step surgical technique using a subcoronal buccal mucosal graft (BMG) resurfacing technique for the treatment of recurrent penile adhesions. Methods: To perform the 'buccal belt' procedure a subcoronal circumferential segment of diseased skin was excised. An appropriately sized BMG was circumferentially secured subcoronally with a proximal and distal anastomosis to the edges of the wound. Quilting stitches were also placed to allow proper graft fixation. A petroleum jelly bolster was secured as a tie‐over dressing. Patients were discharged with a Foley catheter and the bolster dressing in place. The bolster and Foley catheter were removed 7 days postoperatively. The patients were then seen for follow‐up at 4‐ to 6‐month intervals. A retrospective, international multi‐institutional review was conducted to include all patients who underwent this procedure. Surgical complications, evidence of recurrence, and patient‐reported outcome measures including visual analogue scale (VAS) and global response assessment (GRA) questionnaires were reviewed. Results: Thirty‐one men underwent the procedure across six institutions between March 2014 and September 2020. The mean (range) surgical time was 59 (25–95) min. At the mean (range) follow‐up of 27 (4–79) months all patients reported resolution of presenting symptoms and no recurrence of adhesions. The mean VAS score was 8.9 and 9.0 for aesthetics and functional outcomes, respectively. On GRA, overall improvement was reported by all patients (61%, +3; 25%, +2; 14%, +1). Conclusion: There are limited options for the treatment of recurrent penile adhesions. A subcoronal BMG resurfacing is feasible, with no recurrence and overall high satisfaction seen in an initial patient cohort.